Educação permanente em saúde em unidades críticas de um hospital de ensino: elaboração de material de apoio - Valente, Drieli da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study has had as a general goal to elaborate supporting material for planning and performing measures in permanent education in nursing in critical hospital units and as specific goals to describe the education practice of permanent education in nursing since the identification of necessities until actions really performed in critical hospital units inside teaching hospitals identifying both facilitators and hindered factors found by supervisory nurses to the practice of permanent education in the studied context. It was qualitative study performed in a hospital that serves as a reference recognized in health, in the countryside of São Paulo state, with the involvement of seven working nurses in supervisory duty in one of the critical units, that accepted to take part as volunteers answering to guiding questions by the means of interview according to the resolution of the National Council of Health 466/12 and decision 607.299 of the Committee on Ethics on Research. The treatment given was performed according to the Content Analyses and the outcomes represent a profile of professionals specialized in the area, females in average 30 years, working in the Institution for more than 5 years and working in supervisory function higher than 2 years. In what is related to the practice of permanent education experienced and elaborated by nurses in critical hospital unit, the emerging categories were: Origin of educative actions; developed actions; Reached Outcomes by the staff; facilitators and hidered Factors in the process; and nurses perspectives about the practice of Permanent Education in Health in Critical Units. This way, based in literature and official documents about the theme of Permanent Education in Health and, from the knowledge acquired from experiencing by supervisory nurses in critical units, it was elaborated material for planning and performing of actions in Permanent Education in Nursing in Critical Hospital Units, named ...

Este estudo teve como objetivo geral elaborar material de apoio para planejamento e execução das ações de educação permanente em enfermagem de unidades críticas hospitalares e objetivos específicos descrever a prática de educação permanente em enfermagem desde a identificação de necessidades até ações concretizadas em unidades críticas de um hospital de ensino, identificando fatores facilitadores e dificultadores encontrados por enfermeiros supervisores para a prática de educação permanente no contexto estudado. Foi um estudo qualitativo realizado num hospital de referência reconhecida em saúde, no interior do Estado de São Paulo, com a participação de sete enfermeiros atuantes no cargo de supervisão em unidades críticas, que aceitaram participar voluntariamente, respondendo a questões norteadores, por meio de entrevista, de acordo com a Resolução do Conselho Nacional de Saúde 466/12 e parecer 607.299 do Comitê de Ética em Pesquisa. O tratamento dos dados foi realizado segundo a Análise de Conteúdo e os resultados representam um perfil de profissionais especializados na área, sexo feminino, com idade média de 30 anos, tempo de trabalho na instituição superior a 5 anos e tempo na função de supervisor maior de 2 anos. No que se refere a prática da educação permanente vivenciada e elaborada por enfermeiros de unidades críticas hospitalares, as categorias emergentes foram: Origem da ações educativas; Ações desenvolvidas; Resultados alcançados pelas equipes; Fatores facilitadores e dificultadores no processo; e Perspectivas dos enfermeiros sobre prática da Educação Permanente em Saúde em unidades críticas. Deste modo, com base na literatura e documentos oficiais sobre o tema da Educação Permanente em Saúde e, a partir do conhecimento adquirido das experiências vivenciadas pelos enfermeiros supervisores de unidades críticas, foi elaborado material para planejamento e execução das ações de...
Permanent education in health in critical units of a teaching hospital: preparation of supporting material
Keywords: Educação permanente; Prática profissional; Enfermagem - Orientação profissional; Enfermagem - Pratica; Cuidados em enfermagem - Planejamento; Nursing as a profession; Continuing education